THE INFLUENCE OF GLYCEROL ADDITION AND THERMAL TREATMENT DURATION ON THE CHARACTERISTICS OF EDIBLE FILM BASED ON KOLANG-KALING (Arenga pinnata) - Tunnisa, Haura; Syafruddin, S; Nanda, Satria (Politeknik Negeri Lhokseumawe, 2025)
Research on the production of edible film from kolang-kaling with variations in glycerol addition and heating duration has been conducted with glycerol concentrations of 0; 0.5; 1; 1.5; and 2 mL, and heating times of 5, 10, 15, 20, and 25 minutes at a temperature of 70°C. This study aims to determine the effect of glycerol addition and heating duration on the characteristics of kolang-kaling edible film with the addition of Carboxymethyl Cellulose (CMC). The results showed that the best characteristics were obtained with the addition of 1 mL of glycerol with a heating time of 20 minutes, resulting in a film thickness of 0.053 mm, WVTR of 3.4632 g/m²/day, tensile strength of 14.316 MPa, biodegradability of 52.53%, and initial thermal degradation temperature of 257.66°C. Based on these results, the edible film from kolang-kaling has the potential to be used as an alternative eco-friendly food packaging to replace single-use plastic. Keywords: CMC, Edible Film, Glycerol, Kolang-kaling, Heating